EVALUATION OF THE STRATEGIC POLICIES OF THE JOKOWI GOVERNMENT VOLUME 2 - Lailiyah, Faizzatul; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to determine the extent to which the evaluation of the policy has successfully achieved national goals and provided tangible benefits for the community. The main focus of this research is to measure the extent to which Jokowi's second-term strategic policy has successfully achieved national goals and provided real benefits for the community. Method: This research uses a qualitative descriptive approach, which includes six main indicators: effectiveness, efficiency, adequacy, accuracy, respon-siveness, and equity. Data was obtained through documentation studies in the form of official government reports, regulations, documents, the National Medium-Term De-velopment Plan 2020-2024, as well as evaluations of national strategic pro-jects. Results: The research results show that the six indicators have been well im-plemented. Effectiveness can be seen from the success of the program, program effi-ciency is assessed based on the program's ability to utilize existing resources, adequa-cy can be evaluated from the outcomes of a program in addressing existing issues, accuracy is judged by the success of improvements in various involved sectors, re-sponsiveness is evaluated from the success in addressing public complaints, and equi-ty is assessed by programs that can reach all layers of society.  Novelty: The novelty of this research is evident from the effort to conduct a comprehensive evaluation of the strategic policies of Jokowi's second term government.